Finned spacer panel system for fouling control in Chlorella vulgaris harvesting - Ain Nabilah, N.N. (Institute of Physics Publishing, 2020)
Membrane filtration has been proved as a viable harvesting candidate to harvest microalgae for biofuels application. Though largely limited by membrane fouling that lowers overall process efficiency. The novel finned spacer is proposed to reduce fouling control in Chlorella vulgaris harvesting. The assessment of this work is focusing on these aspects: evaluation performance of finned spacer in directing air bubbles toward the membrane surface, study the effect of fin's gap on membrane fouling control perfor mance, the impact of aeration rate on membrane fouling control and operation under fins switching mode. Effectiveness of finned spacer has been obviously proved by its function to direct and encourage air bubbles toward the membrane surface thus improve their contacts and their foulant scouring impact. The projection of air bubbles is more effective at the narrowest fins gap applied of about 2cm gap. The increasing aeration rate proportionally increases flux of 90 L/(m2.h) at 1.5 L/min aeration. Switching mode was applied to increase module packing density without reducing specific membrane performance. It was found effective at periods of below 5 min. Overall results are very encouraging and promising to obtain significant improvement in fouling control for C. vulgaris filtration. Further study on fundamental aspects as well as parameters optimization can still be done to increase the finned spacer efficiency. Â© Published under licence by IOP Publishing Ltd.